THE MOST SIGNIFICANT MUSICAL INFLUENCES ON ROMANIAN COMPOSERS DURING THE STALINIZATION YEARS - VĂDUVA, Lois Paula (Studia Universitatis Babes-Bolyai Musica, 2019)
During the first half of the 20th century, Romanian music flourished through the creation of a group of composers that were of great value. This generation of artists, although formed in schools of the West, kept in touch with the Romanian culture and worked to develop it and promote it. In this context, the consequences of World War II meant that Romania fell under Soviet control, and as a result, the Soviet ideology encroached on all aspects of Romania's society. The communist authorities realized the potential influence that culture and the arts could have, thus subjugating them to the new social-realist agenda. This paper explores the impact that the Stalinization period had on Romanian composers and the music they created, from censure to monitoring and, ultimately, control.